Contemporary christologies : a Fortress introduction - Schweitzer, Don, 1958- (Fortress Press, 2010)
While many know of the signal contributions of such twentieth-century giants as Paul Tillich or Karl Barth or Pierre Teilhard de Chardin, the important work since their time often goes unremarked until some major controversy erupts. Here is a smart and helpful survey of the chief approaches and thinkers in today's understanding of the person, significance, and work of Jesus Christ. Schweitzer offers an insightful introduction to the contemporary context of Christology, in which basic questions in the discipline (and soteriology) are being rethought in light of globalization, postmodernity, and.